Potential Development of Purwoceng (Pimpinella pruatjan Molk or Pimpinella alpine Kds) Plant Scale Industry Using In-Vitro Culture Technique By Means of Rooting Induction - Egi Nuryadin; Alyaa Nabiila (Journal of Tropical Biodiversity and Biotechnology, 2018)
Purwoceng (Pimpinella pruatjan Molk or Pimpinella alpine KDS) belongs to the Apiaceae family, is an endemic plant in mountainous areas such as the Dieng Plateau, Pangrango Mountain, and mountainous areas in East Java. Parts of the plants, especially roots are efficacious as aphrodisiacs, diuretic drugs and tonics. Based on CITES, this plant belongs to the category of endangered species, so its presence is very rare in nature. This scarcity occurs due to the purwoceng exploitation in nature as traditional herbal medicine without any cultivation or rejuvenation. In situ conservation efforts are almost impossible because the original habitat of this plant has become extinct. Thus, ex situ conservation is more suitable to be applied, by using in-vitro culture techniques. Therefore, a research study is needed on the development of tissue culture techniques in the production of the seeds. Methods of data collection in this study was conducted by literature studies. Therefore, ex-vitro root induction techniques are applied currently, namely rooting induction. The content of the chemical compounds and various properties make purwoceng as a commodity in the raw materials of drugs that have great potential to promote industrial players in the economic field. Based on the results from the literature, the authors can conclude that the potential of purwoceng plants is quite large, but still constrained by the scarcity of seed supply so the application of ex-vitro root induction techniques in in-vitro culture can be a solution in limitation of supply of purwoceng crops for industrial scale. Purwoceng (Pimpinella pruatjan Molk or Pimpinella alpine KDS) belongs to the Apiaceae family, is an endemic plant in mountainous areas such as the Dieng Plateau, Pangrango Mountain, and mountainous areas in East Java. Parts of the plants, especially roots are efficacious as aphrodisiacs, diuretic drugs and tonics. Based on CITES, this plant belongs to the category of endangered species, so its presence is very rare in nature. This scarcity occurs due to the purwoceng exploitation in nature as traditional herbal medicine without any cultivation or rejuvenation. In situ conservation efforts are almost impossible because the original habitat of this plant has become extinct. Thus, ex situ conservation is more suitable to be applied, by using in-vitro culture techniques. Therefore, a research study is needed on the development of tissue culture techniques in the production of the seeds. Methods of data collection in this study was conducted by literature studies. Therefore, ex-vitro root induction techniques are applied currently, namely rooting induction. The content of the chemical compounds and various properties make purwoceng as a commodity in the raw materials of drugs that have great potential to promote industrial players in the economic field. Based on the results from the literature, the authors can conclude that the potential of purwoceng plants is quite large, but still constrained by the scarcity of seed supply so the application of ex-vitro root induction techniques in in-vitro culture can be a solution in limitation of supply of purwoceng crops for industrial scale.